The pre-interventional psychiatric history: an underestimated confounder in benign intracranial lesions studies - Wenz, Holger; Groden, Christoph (Clinical neurology and neurosurgery, 2015)
Objectives: The current study was designed to analyze the influence of a positive pre-interventional psychiatric history on the quality of life (QOL) after successful treatment of benign intracranial extra-cerebral lesions. Methods: Patients treated due to meningioma WHO I or unruptured intracranial aneurysms in two German neurosurgical centers between 2007 and 2013 were screened for exclusion criteria including malignant/chronic diseases, recurrence of the tumor/aneurysm and neurological deficits among others. 131 patients who met the criteria of an objectively unaffected health status were included. The pre-interventional psychiatric histories and the rates of post-interventional headaches, sleeping disorders, symptoms of chronic fatigue syndrome (CFS), post-traumatic stress disorder (PTSD) and QOL were determined by questionnaires which were mailed to the patients. Results: 103 patients returned the questionnaires. Despite the objectively unaffected health status, the patients with a positive pre-interventional psychiatric history demonstrated a post-interventionally significantly lower QOL (p=0.002), a significantly higher Pittsburgh Sleep Quality Index sum score (p=0.009), as well as significantly higher rates of symptoms of a chronic fatigue syndrome (p=0.003) and PTSD (p=0.024), compared to the patient collective with a negative pre-interventional psychiatric status. Conclusion: The results of the current study demonstrate the importance of taking the pre-interventional psychiatric history as a significant and independent confounder into consideration when evaluating the outcome after treatment of benign intracranial extra-cerebral lesions. A pre-interventional psychiatric screening and an early psychological intervention might help to improve the overall outcome after successful treatment of such lesions.